Single Index Model in Forming the Optimal Portfolio Before and During the Covid-19 Pandemic on LQ-45 Shares. - Vita Indriani Wahyuningsih; Chriestie E.J.C. Montolalu; Tohap Manurung (Sam Ratulangi University, 2021)
Investment is a commitment to place a number of funds in an asset to gain benefits in the future. but there will be unexpected risks in investment such as the covid-19 pandemic. a strategy to minimize the risk is to form a portfolio. This study aims to form an optimal portfolio before and during the covid-19 pandemic on LQ-45 shares along with the proportion of funds for each share obtained using a single index model. The data used are in the form of daily stock closing prices, JCI price, and risk-free interest rates. The results of this research get a combination of six stocks and the proportion of funds for data before covid-19 are BTPS gets 15.61%, MNCN gets 6.69%, EXCL gets 19.89%, CTRA gets 9.81%, ICBP gets 10.62%, BBCA gets 37.38% and four stocks combination and the proportion of funds for data during covid-19 are INCO gets 30.09%, ANTM gets 27.54%, INKP gets 22.81%, KLBF gets 19.56%. INCO, ANTM, INKP, KLBF shares can be considered by investors in making investment decisions during the covid-19 pandemic.